The authority vs. the Orthodox Church – historical and contemporary role of the Russian Orthodox Church as an actor in the political system - Natalia Sienko (Facta Simonidis)
In this article devoted to the relationship between the authority and the Russian Orthodox Church on the canvas of history. The author demonstrates the influence of historical experiences and the role of the Russian Orthodox Church on the current model of relations between secular and spiritual authority. An important part of the work is the assessment of the opportunities and threats stemming from the subordination of the Russian Orthodox Church to the current elites.